Multimodality imaging in the diagnostic management of concomitant aortic stenosis and transthyretin-related wild-type cardiac amyloidosis - Cersosimo, Angelica; Bonelli, Andrea; Lombardi, Carlo M.; Moreo, Antonella; Pagnesi, Matteo; Tomasoni, Daniela; Arabia, Gianmarco; Vizzardi, Enrico; Adamo, Marianna; Farina, Davide; Metra, Marco; Inciardi, Riccardo M. (Frontiers in Cardiovascular Medicine, 2023)
Severe Aortic Stenosis (AS) is the most common valvular heart disease with more than 4% of prevalence in 75 year-old people or older. Similarly, Cardiac Amyloidosis (CA), especially “wild-type transthyretin” (wTTR), has shown a prevalence from 22% to 25% in people older than 80 years. The detection of concomitant presence of CA and AS is challenging primarily because of the similar changes on left ventricle (LV) caused by AS and CA, which shares some morphological characteristics. The aim of this review is to identify the imaging triggers in order to recognize occult wtATTR-CA in patients with AS, clarifying the crucial step of the diagnostic process. Multimodality imaging including echocardiography, cardiac magnetic resonance, cardiac computed tomography and DPD-scintigraphy will be analyzed as part of the available diagnostic work-up to early identify wtATTR-CA in patients with AS